Cross-Seasonal Storage of Flue Gas Waste Heat from Power Plants Based on Soil Heat Storage Using Buried Pipes: Geotechnical Thermal Response Experiment - Fan Yang; Ming Liu; Yu Shen; Lijun Zheng; Xinyue Fang; Siming Ma (Energies)
A large amount of low-grade waste heat (flue gas waste heat) cannot be fully utilized in thermal power plants in non-heating seasons; therefore, this study combines cross-seasonal heat storage technology with the cross-seasonal storage of low-grade waste heat in power plants. We propose a cross-seasonal underground heat storage and gas turbine co-generation coupling system to recover low-grade waste heat and large-scale cross-seasonal space–time migration and utilization. The basic law of soil heat storage and release was elucidated through a geotechnical thermal response experiment. The results show that the initial average temperature of the rock and soil mass within a depth range of 0–300 m in the study area was 16.7 °C, λ was 1.97 W/(m∙K), Cv was 2655 kJ/(m3∙K), and R was 0.353 (m∙K)/W. An increase in the operating share decreases unit heat transfer per linear meter of buried pipe heat exchanger. The heat release per unit linear meter increases with the average temperature of the circulating medium in the heat release mode. Similarly, the heat absorption per unit linear meter increases with the rock and soil temperature in the heat absorption mode.